Description of an eye barotrauma in scuba diving with clinical discussion - Barreiros, Pedro (2017)
In this paper we report and discuss a scuba diving accident caused by compression of the mask at a depth of 9.1 m resulting in conjunctiva haemorrhage of both eyes in a 21-year-old male. After five weeks and benefiting from immediate post-accident medical attention and medication followed by ophthalmologic examinations the patient recovered with no chronic effects neither in vision nor in the eyes.